2017
DOI: 10.3892/etm.2017.4603
|View full text |Cite
|
Sign up to set email alerts
|

Increased bone morphogenetic protein-6 in follicular fluid and granulosa cells may correlate with fertilization and embryo quality in humans

Abstract: Abstract. Bone morphogenetic protein-6 (BMP-6), which is a member of the transforming growth factor-β superfamily, is associated with the regulation of bone development and various physiological processes. In the present study, the expression of BMP-6 in follicular fluid and granulosa cells (GCs) from pregnant and non-pregnant patients was explored. A total of 44 pregnant patients (pregnant group) and 36 non-pregnant patients (non-pregnant group) were recruited for the present study. The expression of BMP-6 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…But there was no significant difference between mothers with daughters and mothers with sons in PPARγ protein level (P=0.12). These two proteins are the most important indicators for determining fertility (17,44,45). Therefore, in the study, their effect on determining the gender of the child was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…But there was no significant difference between mothers with daughters and mothers with sons in PPARγ protein level (P=0.12). These two proteins are the most important indicators for determining fertility (17,44,45). Therefore, in the study, their effect on determining the gender of the child was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…BMP‐6 is expressed in oocytes and cumulus cells and acts by increasing AMH and FSH receptor expression, decreasing StAR and GDNF expression, suppressing luteinization by decreasing progesterone production, 6,35,36 so making their participation in good oocyte quality unquestionable. We demonstrated that BMP‐6 had relatively decreased gene expression in the group of infertile women with endometriosis and this finding could be better explored by studying the oocyte competence in this subgroup of women.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria were patients who experienced IVF-ET due to infertility caused by tubal factors or male factors (varying degrees of oligospermia, asthenia, and teratozoospermia, but not azoospermia) or both, with an age ≤ 38 years, regular menstruation (cycle 21–35 days, period 2–8 days, menstrual volume 20–60 ml) 55 , basic FSH < 10 IU/L, first-cycle COS or repeated COS for 3–5 cycles. The exclusion criteria were the same as those in the previous study 56 : patients who were unsuitable for pregnancy due to conditions such as uterine abnormalities or serious heart diseases and who suffered from serious mental disorders, urinary and reproductive system infection, sexually transmitted diseases, endometriosis, uterine fibroids, tuberculosis, uterine adhesion, endometrial lesions, polycystic ovary syndrome, ovarian cyst, and hydrosalpinx. Patients who had been exposed to teratogenic radiation or poison and who were within the action period of the drugs were also excluded.…”
Section: Methodsmentioning
confidence: 99%